Cultural identity expressions through visual analysis in post-disaster housing - Ahmad, Mohd. Hamdan (Science Publications, 2010)
Problem statement: The incidence of natural disasters as well as followed human beings' efforts for reestablishing life is considered as unavoidable essence of nature. Whilst, the interdisciplinary theme of post disaster recovery and reconstruction has been researched worldwide in order to examine its different aspects. And within architectural interests, evaluating the housing reconstruction programs would lead to beneficial clues through which useful lessons may be learnt in terms of reconstruction management while facing such unexpected challenges. Approach: This study aimed to present the visual results of the field work survey based on the mixed method research regarding post-Bam 2003 earthquake housing reconstruction efforts. In fact, the whole study was designed to find out the relation between the attitude of survived households toward their new built homes and the degree of their participation in housing reconstruction process. The focus was on analyzing the selected captured photographs provided to support the findings as documentation of research observations. Results: Accordingly, photographs were organized in to certain categories used as a mode of interpretation within the structure of visual research method analysis. The results indicated that despite different meanings of home to households, their active participation in new housing would accelerate the recovery process from sense of loss caused by catastrophes. Besides, hereby the visual and abstract tools and objectives used by households in order to express their feelings and attitude toward new built homes was addressed within defined method. Conclusion: The results indicated that despite various limitations causing change in local housing pattern following Bam earthquake, residents have attempt to express their cultural identity in some degrees as linkage to lost settings.